A model of reporting and controlling outbreaks by public health agencies - Saak, Alexander E.; Hennessy, David A. (International Food Policy Research Institute, 2016)
When an outbreak of an infectious disease is suspected, a local health agency may notify a state or federal agency and request additional resources to investigate and, if necessary, contain it. However, due to capacity constraints, state and federal health agencies may not be able to grant all such requests, which may give an incentive to local agencies to request help strategically. We study a model of detection and control of an infectious disease by local health agencies in the presence of imperfect information about the likelihood of an outbreak and limited diagnostic capacity. When diagnostic capacity is rationed based on reports of symptoms, the decision to report symptoms or not creates a trade-off. On the one hand, rigorous testing allows one to make an informed disease control decision. On the other hand, it also increases the probability that the disease will spread from an untested area where fewer precautionary measures are taken. Symptoms are overreported (respectively, reported truthfully, or underreported) when the cost of disease control is sufficiently small (respectively, in some intermediate range, or sufficiently large). If the disease incidence decreases or infectiousness increases, symptoms are reported less frequently. If the precision of private signals increases, the extent of overreporting of symptoms may increase. For different values of the parameters it can be socially optimal to subsidize or tax requests for additional investigations and confirmatory testing.